Time and Necessity in Avicenna’s Theory of Demonstration* - Strobino, Riccardo (Oriens, 2015)
Avicenna’s (d. 1037) theory of demonstration is largely inspired by Aristotle’s Posterior Analytics but also, at the same time, characterized by significant flashes of originality. One of the areas where Avicenna’s innovative contribution is most evident is his interpretation of the notion of necessity in the context of demonstrative arguments. The paper investigates two issues. First, the relationship between the notion of substantial necessity and that of descriptional necessity and their relevance for Avicenna’s theory of scientific discourse. Second, the question whether Barbara LXL qualifies as a genuine demonstrative argument, i.e., whether its combination of modalized premises provides sufficiently strong epistemic grounds for certitude to come about in the conclusion of a syllogism.